Metonymy Basted on the Prespective of Rhetoric - محمد غلامرضایی (مطالعات زبانی و بلاغی)
Metonymy is the most important notion in rhetoric and exquisite and even, as seen by some scholars the whole of it. In rhetoric and exquisite, one part of metonymy, individual metonymy, falls into rhetoric and the other part, compound metonymy, falls into requisite.